Chemo-selective Rh-catalysed hydrogenation of azides into amines. (March 2020) - Ghirardello, Mattia; Ledru, Helene; Sau, Abhijit; Galan, M. Carmen
Abstract: Rh/Al2 O3 can be used as an effective chemo-selective reductive catalyst that combines the mild conditions of catalytic hydrogenation with high selectivity for azide moieties in the presence of other hydrogenolysis labile groups such as benzyl and benzyloxycarbonyl functionalities. The practicality of this strategy is exemplified with a range of azide-containing carbohydrate and amino acid derivatives. Graphical abstract: Image 1 Highlights: Rh/Al2 O3 can be used as a mild and effective chemo-selective reductive catalyst for azide moieties. The method is chemoselective to azides in the presence of other hydrogenolysis labile groups (-OBn, -Cbz). The reactions proceed cleanly and across a range of reactivity profiles.